THE INFLUENCE OF SOCIO-ECONOMIC FACTORS, INNOVATION ATTRIBUTES, AND FARMER PARTICIPATION ON THE IMPLEMENTATION OF THE JAJAR LEGOWO PLANTING SYSTEM (Oryza Sativa L.) IN PATEBON DISTRICT, KENDAL REGENCY - Maidaliana; Setia Budi; Jamilah (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study examined the influence of socio-economic factors, innovation attributes, and farmer participation on the adoption of the jajar legowo planting system in Patebon District, Kendal Regency, where the technology has not been fully adopted by rice farmers despite its potential to improve rice productivity. A quantitative descriptive approach with binary logistic regression analysis was employed. Data were collected through interviews and Likert-scale questionnaires administered to 62 rice farmers, consisting of 28 adopters and 34 non-adopters of the jajar legowo planting system. The descriptive analysis showed that social factors, economic factors, innovation attributes, and farmer participation were generally in the good category. Logistic regression analysis revealed that economic factors and innovation attributes significantly influenced the adoption of the jajar legowo planting system, whereas social factors and farmer participation had no significant effect. These findings indicate that farmers are more likely to adopt the system when they perceive clear economic benefits and practical advantages from the innovation. Therefore, strengthening farmers’ understanding of innovation benefits and improving economic incentives are important strategies for increasing the adoption of the jajar legowo planting system and supporting sustainable rice production. Keywords: Adoption, Farmer Participation, Innovation Attributes, Jajar Legowo, Socio-Economic Factors